Comportamento alimentar do camarão de agua doce, Macrobrachium rosenbergii (De Man) (Crustacea, Palaemonidae) durante a fase larval: análise qualitativa - Barros, Helenice P [UNESP] (1997)
Feeding behavior of the larvae's prawn, Macrobrachium rosenbergii de Man, 1879, in each stage of development was studied face alArtemia Linnaeus, 1758 nauplii, dry and wet diets. Groups of ten larvae in each stage were placed in 500 ml beakers at 29ºC in filtered brackish water. After the fasting period of acclimatization, the three types of food were offered separately to the larvae and the feeding behavior was observed during 30 min. Feeding perception, capture, grasp and ingestion of food were used to determine feeding pattern. Stage I lawac do not eat. The feeding behavior of larvae was similar on the stages II - XI. The perception in distance does not occur in most individuais; the feeding process generally started with the physrcal contact of food with the animal. Food is captured by thoracic appendages (maxillipeds until stage III, and maxillipeds + pereopods in stages IV - XI) and particles are grasped and handled by maxillipeds. Inopposition at the capture, the ingestion is a seletive process. Selective responses decrease in later stages and larvae become omnivorous in greater degree.